Spinal macrophage migration inhibitory factor and high mobility group box 1 mediate persistent bladder pain. (23rd April 2019) - Ma, Fei; Meyer-Siegler, Katherine L.; Leng, Lin; Bucala, Richard; Vera, Pedro L.
Highlights: Persistent bladder pain is associated with spinal changes in MIF HMGB1 levels. Spinal MIF mediates repeated PAR4 instillation induced persistent bladder pain. Spinal HMGB1 mediates repeated PAR4 instillation induced persistent bladder pain. Abstract: Repeated intravesical PAR4 (protease activated receptor 4) activation elicits persistent bladder pain lasting 5 days after the last treatment. Persistent bladder pain was fully reversed by a systemic HMGB1 (high mobility group box 1) inhibitor while a MIF (macrophage migration inhibitory factor) antagonist partly reversed it. Since there is growing evidence that spinal MIF and HMGB1 mediate inflammatory and neuropathic pain we examined whether there were spinal changes occurring during persistent bladder pain that may be responsible for maintaining bladder pain. In addition, we tested whether we could modulate persistent bladder pain with spinal MIF or HMGB1 antagonists. Persistent bladder pain was elicited in female C57 mice by repeated (3x) intravesical instillation of PAR4-activating peptide while control animals received scramble peptide treatment. On day 4, spinal cord (L6-S1) changes in c-fos (non-specific marker of spinal activation) was assessed with immunofluorescence while MIF and HMGB1 were assessed with immunofluorescence, western blotting and real-time PCR. On day 7, mice received an intrathecal injection of a neutralizing MIF monoclonal antibody (15 μg in 5 μl PBS) or a HMGB1 inhibitor glycyrrhizin (25 μg in 5 μl of 5% alcohol in PBS) and abdominal mechanical threshold was tested. On day 9, mice were treated with vehicle or control and abdominal mechanical threshold was tested. Immunofluorescence showed that c-fos and MIF in the dorsal horn, dorsal grey commissure and intermediolateral areas significantly increased in PAR4-treated mice while HMGB1 was decreased. In addition, intrathecal treatment with MIF neutralizing mAb or glycyrrhizin significantly alleviated abdominal mechanical hypersensitivity at 1 and 2 h and the analgesic effect diminished at 6 h. Vehicle or control treatment had no effect. Persistent bladder pain is associated with spinal changes in MIF and HMGB1 levels. Furthermore, spinal treatment with MIF monoclonal antibody and HMGB1 inhibitor temporarily reversed bladder pain. Our findings suggest that spinal MIF and HMGB1 participate in persistent bladder pain induced by repeated intravesical PAR4 and may be potential therapeutic targets in chronic bladder pain conditions.